Efficacy and safety of anti-thrombotic therapy after surgical mitral valve repair: a scoping review - Jian Ye; Jenny Chen; Hazal Ece Babadagli; Ricky Turgeon; Erica HZ Wang (Open Heart)
Background Mitral valve repair (MVr) is the gold standard treatment for degenerative mitral regurgitation, yet there is ongoing controversy regarding optimal anti-thrombotic therapy post-MVr. This scoping review aimed to summarise current evidence on the safety and efficacy of anti-thrombotic therapy after MVr, identify knowledge gaps and propose a future study design.Methods We searched MEDLINE, Embase, Cochrane Central Register of Controlled Trials, Clinicaltrials.gov, the WHO International Clinical Trials Registry Platform and bibliographies of included trials, guidelines and other reviews from inception to 17 September 2024. Randomised controlled trials (RCT) and cohort and case-control studies assessing any anti-thrombotic therapy with any outcomes after MVr were included. Using a predefined collection form, two authors independently extracted data on study characteristics and results were summarised narratively into themes based on the PICO elements.Results Of 1296 screened references, we included 11 studies (10 cohort and one non-inferiority RCT). All studies compared vitamin K antagonist (VKA) to an anti-platelet, direct oral anti-coagulant or no anti-thrombotic therapy for median duration of 90 days. Thromboembolic and bleeding event incidences ranged from 0% to 14.3% and 0% to 9.1%, respectively. Seven studies reported no difference in thromboembolic events, and three reported reduced rates with VKA compared with control, while results for bleeding events varied widely. The RCT found edoxaban was non-inferior to warfarin for thromboembolic outcomes, but not for bleeding. Substantial methodological and clinical heterogeneity, high risk of bias and insufficient mitigation of confounders, such as concomitant atrial fibrillation, were prevalent across studies.Conclusion Based on this scoping review, existing literature on anti-thrombotic therapy after MVr is inconclusive due to design limitations. We proposed a study design for a pragmatic RCT that addresses prior study limitations and that could provide definitive evidence to guide anti-thrombotic management in MVr patients.